Implications of the Determination of the Center for Industrial Growth on Land Use in Tanjung Balai City - Jhon Markus Sembiring; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to examine the Implications of the Determination of the Industrial Growth Center Area on Land Use in Tanjung Balai City. Research on complex and wide-impact land use changes such as in Tanjung Balai should use a descriptive qualitative method, with in-depth interviews, observations, and document analysis techniques. An inductive approach in data analysis as well as triangulation and participatory involvement from the community will also increase the validity and accuracy of research results. With this approach, it is hoped that the research can provide a comprehensive overview of the impact of land conversion for industrial purposes and become a valuable input for sustainable policy formulation in Tanjung Balai. The results of the research Land use change for industry poses challenges in urban spatial planning and management. The need for public infrastructure, such as roads and drainage channels, has increased in line with industrial development, but has not been fully balanced with adequate planning. This challenge emphasizes the importance of balancing industrial development and the needs of settlements and green open spaces. In order for the negative impact of the designation of industrial zones to be minimized, it is recommended that the Tanjung Balai City Government implement sustainable spatial planning policies and consider the balance between economic development and environmental conservation. Measures such as strict monitoring of industrial waste, provision of green infrastructure, and training programs for communities affected by land conversion can help improve the quality of life of communities and preserve the environment in the midst of industrial development.